Studi Komparasi Sejarah dan Aturan Kalender Tahun Masehi: Julian dan Gregorian - Farah, Labibah Amil; Saifulloh, M.; Roesuldi, Juhanda (Universitas Islam Negeri Mataram, 2022)
The common era calendar was a calendar from the ancient Roman calendar that uses lunar system that Julius Caesar then modified on sosignes' suggestion to use the solar system as the with one year's tropical length to 365.25 days. As science progressed, Pope Gregory XIII made improvements by favoring a reference to the tropic count 365.2425 days, shorter by 0.0075 days than Julian. Gregory added new rules and corrections to Julian's calendar to keep the calendar in line with the annual movement of the sun. It also explains how dates are dated before and after the common era.Keywords: calendar, masehi, julian, gregorian, islamic astronomy